Quantitative Imaging of Preamyloid Oligomers, a Novel Structural Abnormality, in Human Atrial Samples. (July 2014) - Sidorova, Tatiana N.; Mace, Lisa C.; Wells, K. Sam; Yermalitskaya, Liudmila V.; Su, Pei-Fang; Shyr, Yu; Byrne, John G.; Petracek, Michael R.; Greelish, James P.; Hoff, Steven J.; Ball, Stephen K.; Glabe, Charles G.; et al.
Abnormalities in atrial myocardium increase the likelihood of arrhythmias, including atrial fibrillation (AF). The deposition of misfolded protein, or amyloidosis, plays an important role in the pathophysiology of many diseases, including human cardiomyopathies. We have shown that genes implicated in amyloidosis are activated in a cellular model of AF, with the development of preamyloid oligomers (PAOs). PAOs are intermediates in the formation of amyloid fibrils, and they are now recognized to be the cytotoxic species during amyloidosis. To investigate the presence of PAOs in human atrium, we developed a microscopic imaging-based protocol to enable robust and reproducible quantitative analysis of PAO burden in atrial samples harvested at the time of elective cardiac surgery. Using PAO- and myocardial-specific antibodies, we found that PAO distribution was typically heterogeneous within a myocardial sample. Rigorous imaging and analysis protocols were developed to quantify the relative area of myocardium containing PAOs, termed the Green/Red ratio (G/R), for a given sample. Using these methods, reproducible G/R values were obtained when different sections of a sample were independently processed, imaged, and analyzed by different investigators. This robust technique will enable studies to investigate the role of this novel structural abnormality in the pathophysiology of and arrhythmia generation in human atrial tissue.